Perception of Teachers, Students & Parent About The Impact of Mid-day Meal Scheme on Improving Health Status of The Students In Punjab - RANI, KANCHAN (Gyan Management Journal, 2019)
Mid Day Meal Scheme is a well-intentioned programme to address all fundamental problems of health,  education and  overall development  of  children in the  country. MDM  could serve as an important  purpose in nurturing the buds and focusing on learning and filling the empty stomach contributing  towards equality. Present study on MDM scheme was carried out to assess the impact of the scheme on  health status of the students in three districts namely Sangrur, Barnala and Mansa of Punjab. Based on  the analysis, suggestions have been recommended for ensuring proper implementation of mid-day  meal  scheme.  The  findings  of  the  study  will  be  of  apparent  interest  to  the  administrators  and  educational policy makers. It also underscores the need for better and more extensive evaluations that  can inform us of the specific appeal of this scheme.
Keywords: Mid-day Meal Scheme; health; nutrition; teachers; Punjab